THE POWER OF CULINARY IN SUSTAINING ACEH ECOLEXICON - Zurriyati Zurriyati; T. Silvana Sinar (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2018)
Ecology is an interrelationship system of the nature. Currently issues on ecological study is on the application of ecological concept within linguistics field that is called eco-linguistics as an interaction between language and its environment for making a balance between natural or original language and the context of culinary culture. This study aims to examine the power of culinary in sustaining Aceh language related to eco-lexicons which focused on the language knowledge of Aceh society including Aceh culinary and eco-lexicons usage. The researcher used qualitative approach with depth interview method and recording techniques. Data were analyzed descriptively with Eco-linguistics interpretation. Ecology aspect includes both cultural and economic value. The sample of this study were Acehnese consist of 25 males and 25 females and one old subject who is professional in cooking.  The techniques of data collection were in depth interview, direct observation, and questionnaires about Kuah Pliek and timphan which are local culinary of Aceh. The results show that Aceh culinary (kuah pliek and timphan) are known 100 % by all of the respondents as the Aceh societies but they have less knowledge about eco-lexicons used as their ingredients and the process of making them.